2017
DOI: 10.15678/aoc.2017.1704
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of R&D Expenditures on Earnings Management

Abstract: The main goal of the paper is to investigate the relationship between R&D spending and earnings management. While R&D expenditures create some of the most precious assets in today's economy, in many accounting jurisdictions they either may not be recognised as an asset in the balance sheet or their recognition is very limited. The main obstacle is the measurement process's lack of reliability, which is the result of information asymmetry caused by the nature of R&D investments. Additionally technological break… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…On the other hand, considering firm size and leverage in terms of control variables in Model 1 and Model 2; it is seen that three models, including the current period, one-year and two-year lag, negatively affect earnings management at 1% significance level. Similarly, Daley & Vigeland (1983), Aboody & Lev (1998), Percy (2000), Landry & Callimaci (2003), Wang & D'Souza (2006), Persson & Fuentes (2011), Guidara & Boujelbene (2015), Dinh et al (2016) and Grabińska & Grabiński (2017), size; Mande et al (2000), Markarian et al (2008), Persson & Fuentes (2011) and Grabińska & Grabiński (2017) revealed that the leverage negatively affects earnings management. In terms of return on assets, considering the current period and time lags, Aboody & Lev (1998), Landry & Callimaci (2003), Markarian et al (2008), Persson & Fuentes (2011) and Dinh et al (2016) contrary to their results, a statistically significant relationship could not be determined.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…On the other hand, considering firm size and leverage in terms of control variables in Model 1 and Model 2; it is seen that three models, including the current period, one-year and two-year lag, negatively affect earnings management at 1% significance level. Similarly, Daley & Vigeland (1983), Aboody & Lev (1998), Percy (2000), Landry & Callimaci (2003), Wang & D'Souza (2006), Persson & Fuentes (2011), Guidara & Boujelbene (2015), Dinh et al (2016) and Grabińska & Grabiński (2017), size; Mande et al (2000), Markarian et al (2008), Persson & Fuentes (2011) and Grabińska & Grabiński (2017) revealed that the leverage negatively affects earnings management. In terms of return on assets, considering the current period and time lags, Aboody & Lev (1998), Landry & Callimaci (2003), Markarian et al (2008), Persson & Fuentes (2011) and Dinh et al (2016) contrary to their results, a statistically significant relationship could not be determined.…”
Section: Resultsmentioning
confidence: 93%
“…It is stated in the literature that the effects of R&D expenditures on earnings management appear in the future (Grabińska & Grabiński, 2017). In this framework, the equation used by Grabińska & Grabiński (2017) was taken as a basis in order to demonstrate the impact of R&D expenditures on earnings management. In terms of R&D intensity, two different R&D variables were obtained by dividing the R&D by total assets (R&D1) and net sales (R&D2).…”
Section: In Equations (2) and (3)mentioning
confidence: 99%
See 2 more Smart Citations
“…The main explanatory variables in the research model are two different R&D intensity measures. These are the ratio of total R&D expenditures to net sales as used in related studies of Wang and Thornhill (2010), Katila and Ahuja (2002), Zhang and Mohnen (2013), and Alessandri and Pattit (2014); and the ratio of total R&D expenditures to total assets proposed by Berrone et al (2007) and, Grabinska and Grabinski (2017). Though the first measure is used more frequently in the literature, this combination is more appropriate, because R&D investments and/or expenditures can be expressed relative to either net sales (as R&D intensity), book value of total assets or equity, market value of equity, net income, or total dividends.…”
Section: Data and Variablesmentioning
confidence: 99%